Utilization of Comprehensive Abortion Care: a community-based cross-sectional study among young people in Tamale Metropolis - Mumuni Alaru; Alhassan Osman; Catherine Kyiu; Faustina Yin Yariga; Mohammed Abdulai Kojo; Ababio-Boamah Christopher; Afia Kwakyewaa Owusu-Agyeman (Journal of Medical Care Research and Review, 2024)
Introduction: Abortion poses a dual challenge as both a medical and social issue, with an estimated 50 million induced (unsafe) abortions occurring annually in developing countries. This study aims to assess the Knowledge, Attitude, and Utilization of Comprehensive Abortion Care (CAC) among young people aged 10 to 24 in the Tamale Metropolis. Methods: A total of 397 young women were recruited through simple random sampling, and a descriptive cross-sectional study design was employed. Data analysis was carried out using SPSS version 25, employing Chi-square analysis for categorical variables. A significance level of p < 0.05 was considered statistically significant. Results: The majority (51.4%) of respondents fell within the 15 to 19 age group, and over 95% had some level of education. While 94.7% were aware of abortion, 67.6% considered it illegal, and merely 3.3% were familiar with CAC services. Media (TV/Radio) played a predominant role (89.5%) as a source of information on CAC. Despite 50.1% knowing someone who had an abortion, CAC utilization remained low (10.1%). Significant associations were found between the use of CAC services was and age (X2=108.4, P<0.001), education level (X2=48.9, P<0.001), and marital status (X2=18.1, P<0.001) Conclusion: The study concludes that despite a good level of knowledge regarding CAC, its utilization among young people is hampered by religious and cultural influences. Media emerged as a crucial source of information on CAC, emphasizing the need for targeted awareness campaigns.